Algorithmic Governance of Online News Policies, Censorship, and accountability: Case of Algeria - BOUTELDJA, Nadjete (Journal of Human Sciences, 2025)
This article contributes to deepening the debate on policies adopted in Algeria to regulate online news content, and explores mechanisms for Censorship, accountability, and transparency. It also seeks to raise the following question: How can algorithmic governance of digital news content be envisioned in the context of Algerian media laws and legislation for 2023? By adopting a qualitative research method that contributes to understanding the technical impact of legal texts, it relies on a deductive approach to extracting phrases and concepts related to algorithms, supported by a critical approach. The study's results confirm that the new laws reflect a growing trend toward regulating digital news content according to specific legal frameworks, indicating that Algerian policy has prioritized human oversight through specialized bodies that monitor news content and impose penalties on violators, with the absence of precise mechanisms to regulate algorithms and hold global digital platforms accountable. To overcome these problems, the study recommends developing media legislation that focuses on artificial intelligence algorithms, promotes international cooperation and joint scientific research.